Molecular identification of colour pattern genes in birds - Schwochow-Thalmann, Doreen (2018)
Birds display a spectacular range of plumage pigmentation. The purpose of this thesis was to elucidate genetic mechanisms that contribute to pattern formation on individual feathers and the body. In study I and II, we investigated two barring patterns in chicken. We show that in the Fayoumi breed autosomal barring is associated with a 1Mb un-recombined region on chromosome 11, which contains the MC1R gene. Our functional analysis strongly suggests that autosomal barring is primarily caused by activating MC1R mutations and that other loci contribute to the appearance of the pattern. In study II, we demonstrate that sex-linked barring is created by a combination of cis-regulatory and missense mutations in the CDKN2A/ ARF gene. We demonstrate that the up-regulation of CDKN2A expression is caused by non-coding mutation(s) and is resulting in a dilute barring pattern. Functional testing revealed that the two missense mutations in ARF hamper its function and restrict the diluting effect of the non-coding mutations. Only the combination of both regulatory and missense mutations generates clear barring pattern as observed e.g. in the Barred Plymouth Rock. In study III and IV, we investigated the genetic mechanisms driving pigment pattern variation in the ruff (Philomachus pugnax). We first identified a 4.5 Mb inversion to be associated with the two male reproductive morphs called satellite and faeder. These morphs differ substantially in behavior, reproductive strategy, body size and plumage appearance between each other as well as from the third, more prevalent morph, the independent. The inversion disrupts the CENPN gene making this genomic re-arrangement homozygous lethal. We identified a large set of variants; among them four missense mutations in MC1R associated with the Satellite allele. In study IV, we explored whether these MC1R mutations are contributing to the light display plumage of the satellite morph. Our data shows that MC1R is up-regulated in all coloured satellite feathers and that this is due to a ...